Impactos socioambientais do uso da biomassa na produção de energia - Souza, Victor Hugo Alves de (2017)
The cultivation of biomass for the production of biofuels and electricity generation has gained increasing importance in society, due to the need for diversification of the national energy and electric matrix, among other aspects. In Brazil, the cultivation of vegetable inputs, such as soybeans and sugarcane, for use in the Brazilian energy industry, has been encouraged through specific sectoral laws and programs. With this in mind, this study aims to analyze the main socioenvironmental impacts of the use of biomass for the generation of energy in Brazil. For that, a qualitative research was chosen, based on bibliographical and documentary research. The conclusions indicate that the use of biomass in this industry, despite the benefits, also presents disadvantages, among them rural exodus, concentration of land use for monocultures, deforestation and the influence of this production on the price of commodities in the international market. Despite the impacts identified in the literature and discussed in this paper, it should be pointed out that the use of biomass contributes to a greater diversification of the national electric and energy matrix, as well as to the mitigation of environmental problems, compared to the use of fuels of origin fossil.